2023
DOI: 10.1108/mhrj-12-2022-0077
|View full text |Cite
|
Sign up to set email alerts
|

Pilot effectiveness trial of Mood Lifters for individuals who self-report bipolar disorder

Elena Lauren Pokowitz,
Cassandra Menzies,
Cecilia Votta
et al.

Abstract: Purpose Bipolar disorder is associated with poor mental and physical health outcomes, and therefore, it is crucial to research and develop effective interventions for this population (Grande et al., 2016). Unfortunately, research on the efficacy of current interventions shows only small improvements in symptoms and quality of life (Oud et al., 2016). Additionally, individuals with bipolar disorder face barriers to accessing care like social stigma, isolation and financial constraints (Blixen et al., 2016). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The Mood Lifters for Graduate Students and Mood Lifters for Young Adults programs seek to support young adults in navigating transdiagnostic mental health and wellness throughout a transitional time in their lives. Previous studies have shown that ML is efficacious and effective in reducing symptoms of psychopathology and promoting mental wellness across various populations and adaptations (e.g., [ 3 , 4 , 7 , 8 , 9 , 10 , 11 ]), yet the mechanism driving these changes has yet to be determined. The current study sought to explore potential mechanisms of change by analyzing participants’ lived experiences of engagement with the ML program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mood Lifters for Graduate Students and Mood Lifters for Young Adults programs seek to support young adults in navigating transdiagnostic mental health and wellness throughout a transitional time in their lives. Previous studies have shown that ML is efficacious and effective in reducing symptoms of psychopathology and promoting mental wellness across various populations and adaptations (e.g., [ 3 , 4 , 7 , 8 , 9 , 10 , 11 ]), yet the mechanism driving these changes has yet to be determined. The current study sought to explore potential mechanisms of change by analyzing participants’ lived experiences of engagement with the ML program.…”
Section: Discussionmentioning
confidence: 99%
“…For individuals experiencing no, mild, or moderate symptoms, ML may function as prevention and/or intervention without the need for other mental health care (e.g., [3]). For those experiencing more severe symptom levels, ML may be adjunctive to other individual or group-based mental health care (e.g., [4]). For detailed information on the ML program and content, see Pokowitz et al, 2024 [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation